Epileptic Seizure development in Participants with Cerebral Venous Sinuses Thrombosis - Hazim Mhmood, Emad (International Journal of Psychosocial Rehabilitation, 2021)
Background: Cerebral venous sinuses thrombosis (CVST) is a condition with multiple etiologies that can complicate to epileptic seizure. The study aimed to determine the incidence of seizure and to estimate the exaggerating factors in participants with CVST. Methods: An observational case-control study enrolled 30 participants with CVST. Data including age, gender, clinical features and focal neurologic signs were collected. Patients were followed up for one year from initial diagnosis to the recognition of epileptic seizure. Results: The mean age of patients was 35.2±14.2 years. Females were represented 70%, whereas males were 30% of the patients. The duration of symptoms of CVST was 9.6±5.5 days with an average hospital admission of 8.4±6.1 days. The most frequent symptom was headache, which documented in 47 (94%) of patients. Regarding MRI brain findings, hemorrhagic lesions found in 32% and infarction in 68%. The superior sagittal and lateral sinuses were the most involved. The changes on MRI, including punctiform foci in 72%, extensive edematous in 50%, the ventricle dilation in 56%, about 48% of CVST presented in acute phase, 40% in subacute phase, and 12% in chronic phase, the majority of foci sized less than 0.5 mm (33, 66%), and the clot appeared hyperintense on T1 MRI in 60%, hyperintense on T2 MRI in 22%, whereas FLAIR picture seen in 18%.There were (5, 10%) patients who had only focal seizures, (10, 20%) experienced generalized seizures, and (5, 10%) suffered a mix of both. There were no significant differences between CVST patients with and without seizures in terms of age, gender, duration of symptoms, and hospitalization. MRI imaging findings, neither hemorrhagic lesion nor infarction showed a significant association with the presence of seizure. Conclusion: Iraqi people are at high risk of developing CVST. There are several signals in CVST patients to the development of seizures as MRI findings and occlusion sites of the sinuses. Awareness needs to rise, and monitoring must be undertaken about the risk factors for the development of seizures in CVST patients.